A new request to the social psychiatry in Ukraine: stress-related disorders and PTSD, are we ready? - Chaban, Oleg (Psychosomatic Medicine and General Practice, 2017)
In early 2014 resulted by the outbreak of conflict in eastern Ukraine 823,000 people became internally displaced, according to the Ukrainian State Emergency Service. All of the above requires a new assessment of the state of people in a situation of chronic stress and distress taking into account their mentality, psychological amortization properties and social situation. We need systematic training of specialists in the field of acute stress and PTSD, with following consistent professional development. It is necessary to develop a national protocol for PTSD management and to implement an appropriate modernization of the Ukrainian health care system.